2017
DOI: 10.1021/acs.iecr.7b00045
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Based Catalysts for the Selective Catalytic Reduction of NOx in the Presence of Excess Oxygen and Simulated Diesel Engine Exhaust Conditions

Abstract: A family of various cerium oxide-based catalysts were synthesized by adopting flame aerosol (FSP), coprecipitation, wet impregnation, and hydrothermal synthesis techniques. The resulting catalysts were explored for the selective catalytic reduction (SCR) of NO x using NH3 as reductant. In our studies, both the preparation method and the Ce/W ratios were found to be critical variables for successful catalyst promotion. For the industrial realization, we have scaled up the SCR activity tests. The microreactor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…It could be resolved into eight components (labeled as v and u, respectively). The bands labeled u′ and v′ represented the 3d 10 4f 1 initial electronic state corresponding to Ce 3+ , whereas the peaks labeled u, u″, u‴, v, v″, and v‴ represented the 3d 10 4f 0 state of Ce 4+ ions . It is a consensus that the presence of more Ce 3+ is beneficial to the SCR reaction because Ce 3+ could create charge imbalance and would lead to vacancies and unsaturated chemical bonds on the catalyst surface, which facilitated in the increase of surface‐absorbed oxygen .…”
Section: Resultsmentioning
confidence: 99%
“…It could be resolved into eight components (labeled as v and u, respectively). The bands labeled u′ and v′ represented the 3d 10 4f 1 initial electronic state corresponding to Ce 3+ , whereas the peaks labeled u, u″, u‴, v, v″, and v‴ represented the 3d 10 4f 0 state of Ce 4+ ions . It is a consensus that the presence of more Ce 3+ is beneficial to the SCR reaction because Ce 3+ could create charge imbalance and would lead to vacancies and unsaturated chemical bonds on the catalyst surface, which facilitated in the increase of surface‐absorbed oxygen .…”
Section: Resultsmentioning
confidence: 99%
“…According to the binding energies of different peaks, the Ce 3d spectra could be elaborately separated into eight peaks, labeled as u, u , u , u and v, v , v , v , respectively [54]. The u and v peaks were matched with the 3d 10 4f 1 electronic state of Ce 3+ , and the u, u , u , v, v , and v peaks were ascribed to the 3d 10 4f 0 electronic state of Ce 4+ [55]. These distinctive peaks verified the coexistence of of Ce 3+ and Ce 4+ species on Mn−Co/TiO 2 nanocatalyst surface.…”
Section: Oxidation States Of Active Speciesmentioning
confidence: 99%
“…Studies in recent years revealed that the presence of rare-earth components can effectively regulate the surface acidity and alkalinity, modify the structure of catalytic active centers, improve the oxygen storage/release capacities, and enhance the structural stability and active species dispersion of catalysts. 13,14 As an important component of rare-earth catalytic materials, CeO 2 is a potential substitute for V 2 O 5 due to its high oxygen storage capacity and redox ability when Ce species shi between Ce 4+ and Ce 3+ . 15 28 Furthermore, SiO 2 is widely used as catalyst supports due to their high mechanical strength and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%